Integrasi Pendekatan Multikultural Dalam PAI: Mempromosikan Toleransi Dan Kerukunan Antarumat Beragama - Irwansuri, Zulfan (Penerbit Goodwood, 2025)
Purpose: This study examines the consequences of neglecting a multicultural approach in Islamic Religious Education (IRE), particularly its impact on tolerance and social harmony in diverse religious communities. The research highlights the risks of conflict arising from insufficient integration of multicultural principles and underscores the urgent need for inclusive educational practices. Research Methodology: The study employs a rigorous library research method by analyzing selected scientific journal articles and research reports related to multiculturalism and Islamic education. The approach emphasizes thematic analysis to identify, interpret, and synthesize key concepts, strategies, and outcomes of multicultural integration in IRE. Results: Findings reveal that deliberate incorporation of multicultural perspectives in IRE is highly effective in enhancing tolerance and interfaith harmony. Anchored in the principles of respect for diversity and pluralism theory, success is achieved through inclusive curricula, educator training in tolerant classroom management, and the promotion of multicultural activities. This integration significantly fosters appreciation for diversity, reduces prejudice, and strengthens social cohesion. Conclusions: A multicultural approach in IRE, grounded in diversity and pluralism, is unequivocally effective in creating inclusive and tolerant learning environments. Its systematic implementation can serve as a foundation for preventing interreligious tensions and promoting sustainable harmony. Limitations: The study is limited to secondary data, relying solely on literature without empirical validation. Hence, its conclusions may not fully capture lived classroom experiences. Contribution: This research underscores the pivotal role of multiculturalism in Islamic education as a catalyst for tolerance and harmony. It provides strategic insights for policymakers and educators to strengthen curricula and practices in diverse learning contexts.